Development and physiological aspects of three species of passion fruit submitted to water stress - Lisboa, Lucas Aparecido Manzani [UNESP]; Cavichioli, José Carlos; Vitorino, Rodrigo Aparecido; Contiero, Leandro Aparecido Fogagnoli; de Figueiredo, Paulo Alexandre Monteiro [UNESP] (Editora Letra1, 2022)
The aim of this work was to evaluate the development and physiological aspects of three species of passion fruit submitted to water stress. The work was carried out at the Faculdade de Ciências Agrárias e Tecnológicas of Universidade Estadual Paulista (Unesp, Brazil). The experimental design was completely randomized (DIC), in a 3 x 3 factorial arrangement, in which three passion fruit species were used: Passiflora gibertii; Passiflora foetida, and Passiflora edulis interacting with three irrigation intervals, namely: 4, 8 and 12 days, with four replications. The suspension of irrigations for twelve days reduces the transpiration of passion fruit seedlings, while the suspension of irrigations every eight days reduces stomatal conductance. Passiflora gibertii plants have higher photosynthetic efficiency than P. edulis and P. foetida. Passiflora gibertii seedlings show greater growth than P. foetida and P. edulis, while P. foetida seedlings have the highest number of leaves. In plants irrigated at twelve-day intervals, fruit growth was affected.
Desenvolvimento e aspectos fisiológicos de três espécies de maracujás submetidas a estresse hídrico.
Keywords: irrigation; Passiflora; stomatal conductance; transpiration